The The Role of Leadership in Improving UC Silver & Gold Employee Performance: English - NI Komang Rada Lestari; Ni Kadek Dessy Hariyanti; Ni Nyoman Terestiyani Winaya (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
Change is a constant in the business world, and effective leadership can Change is a constant in the business world, and effective leadership can help organizations adapt quickly and efficiently. Leaders who are flexible and solution-oriented are able to manage change well, reduce resistance, and accelerate the implementation of necessary changes. The purpose of this research is to determine the role of leadership in employee performance at UC Silver & Gold. This research has theoretical benefits. It is hoped that this research will be able to increase knowledge and insight, especially regarding the influence of leadership in improving employee performance. This research was conducted at UC. Silver & Gold, The sample used in this research was employees and leaders. Data sources were obtained from primary and secondary data for primary data which came from interviews with leaders and employees using management functions as the basis for interview questions, while secondary data was in the form of organizational structure, number of employees, employee performance data and annual production data. . The type of data used is qualitative data which can be defined as data in the form of words, schemes and images. Qualitative data takes time because it goes through interview, observation and observation stages and there are three data analyzes in descriptive analysis, namely including data reduction, data presentation and drawing conclusions.